Physicochemical and Fat-Soluble Vitamins Constituents of Fresh and Reused Vegetable Oil from Abakaliki Metropolis, Ebonyi State - Nwabunma C. Asouzu; Okide Afoma Ifunanya; Patrick M. Aja; Okon Michael Ben; Nonso C. Asouzu; Aja Lucy; Ejike Daniel Eze; Afodun Adam Moyosore; Awuchi G. Chinaza (Jurnal Multidisiplin Madani, 2023)
This research work was designed to evaluate the physicochemical and fat-soluble vitamins constituents of fresh and reused vegetable oils from fast food vendors in Abakaliki Metropolis. The physicochemical constituents such as peroxide value, saponification value, iodine value, acid value, free fatty acid value and fat-soluble vitamins like retinol, tocopherol and phytonadione were determined by standard laboratory procedures. The results of physicochemical constituents of reused vegetable oil showed increased acid value, free fatty acid, peroxide value and saponification value in reused vegetable oil with a drastic decrease in iodine value. The results of fat-soluble vitamins composition of reused vegetable oil showed decreased levels of retinol, tocopherol and phytonadione when compared to fresh vegetable oil from fast food vendors in Abakaliki. The results of the study revealed the poor quality of reused vegetable oil by fast food vendors in Abakaliki Metropolis and such practice should be discouraged for healthy nutrition and diet